2008
DOI: 10.1590/s1413-70542008000600030
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento higroscópico do extrato seco de urucum (Bixa Orellana L)

Abstract: RESUMONeste trabalho, objetivou-se determinar a higroscopicidade do urucum na forma de extrato seco. Neste estudo foram obtidas as atividades de água do extrato seco de urucum para as temperaturas de 10 a 50ºC e teores de água entre 6 e 22% base úmida. A metodologia empregada para as determinações foi o método dinâmico em que se utilizou o equipamento Thermoconstanter Novasina TH-2. Para os resultados experimentais aplicaram-se as equações propostas por Henderson modificada por Thompson e Henderson modificada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
4
1
4
Order By: Relevance
“…EMEPA (0.07 and 0.008 mg.g -1 , respectively) by Anselmo et al (2008), but calcium was lower than that found by Ferreira & Falesi (1989) (1.82 mg.g -1 ).…”
Section: Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…EMEPA (0.07 and 0.008 mg.g -1 , respectively) by Anselmo et al (2008), but calcium was lower than that found by Ferreira & Falesi (1989) (1.82 mg.g -1 ).…”
Section: Resultscontrasting
confidence: 50%
“…This is due to their characteristics as a non-toxic product with high dying power and ample color used for coloring food, products, cosmetics, pharmaceuticals and textiles, besides being used in cooking, as with the Brazilian spice colorau. Brazil is one of the largest producers and exporters of natural dye extracted from this plant (Mantovani et al, 2013;Anselmo et al, 2008). Annato seeds have been used to treat various diseases in popular medicine including for high lipid blood levels (Ferreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este pode ser obtido por processos mecânicos através de atrito ou raspagem das sementes, através de solventes, ou ainda através de processos enzimáticos. Sendo de baixo custo de produção, também conhecido internacionalmente como "annatto", é utilizado em vários setores industriais em substituição a muitos corantes sintéticos (Anselmo et al, 2008).…”
Section: Introductionunclassified
“…Parameters of the models fitted to the hygroscopic equilibrium moisture contents of baru fruits (Dipteryx alata Vogel), with their respective determination coefficients (R 2 , %), estimated mean errors (SE, decimal), relative mean errors (P, %), chi-square (χ 2 , decimal) and trend of distribution of residuals agricultural products: bean (Resende et al, 2006), dry extract of 'urucum' (Anselmo et al, 2008), sweet corn grains , seeds of 'caju-de-árvore-do-cerrado' (Caetano et al 2012), seeds of rice in husk (Oliveira et al, 2014) and seeds of pepper (Silva et al, 2015). Considering that the development of fungi starts with water activity around 0.7 (Oliveira et al, 2005), the water contents recommended for safe storage of baru fruits are, at most, 19.9, 19.3, 18.6 and 18.0 (%, d.b.…”
Section: Resultsmentioning
confidence: 99%